Evolución del consumo y compras de bienes durables en Chile, 1981 - 1999 - Gallego, Francisco; Soto, Raimundo (Estudios de Economía, 2016)
This paper presents a methodology to build series of purchases, consumption,and stocks of durable goods for the Chilean economy in the 1981-1999 period.The estimated series –both nominal and real– are presented in quarterly andannual frequencies. In addition, the paper explores the differences in theirdynamic structure with regards to the evolution of non-durable consumption,interest rates, real wages, employment, and real output.